Adjuvant targeted therapy combined with surgery for advanced and metastatic renal cell carcinoma: A protocol for systematic review and meta analysis. Issue 3 (22nd January 2021) - Jin, Hongyu; Zhang, Man; Jin, Kun; Hu, Chenggong
Abstract: Background: The aim of this systematic review and meta-analysis is to evaluate the efficacy and safety of adjuvant targeted therapy by sunitinib combined with surgery in the treatment of advanced or metastatic renal cell carcinoma. Methods: PubMed/Medline, Web of Science, Cochrane Library, ClinicalTrials.gov (http://www.ClinicalTrials.gov ), China National Knowledge Infrastructure (CNKI) will be searched for clinical research articles related to the efficacy and safety of adjuvant therapy combined with surgery in the treatment of advanced and metastatic RCC. The identification, inclusion and exclusion flow charts will be conducted according to the PRISMA guidelines. The quality assessment will be done by Quadas-2 evaluation tool. Key parameters including OS in 10, 20, 30, and 40 months, PFS in 10, 20, and 30 months, objective response rate (ORR), stable disease (SD) rate, progressive disease (PD) rate, median OS and PFS, types of AEs and their occurrence rates, etc will be extracted. The evaluation of the efficacy and safety will be pooled by CMA. Results: This systematic review will provide evidence on the efficacy and safety of adjuvant therapy by sunitinib combined with surgery in treating advanced and metastatic RCC. Conclusion: The study aims to generalize data concerning the response rate, OS, PFS and rates of adverse effects of the perioperative use of sunitinib in advanced and metastatic RCC patients. The evidence provided by this systematic review and meta-analysis will help guide the clinical decision making and enlighten the future management of advanced or metastatic RCC. Registration: This protocol has been registered on the International Platform of Registered Systematic Review and Meta-analysis Protocols (INPLASY registration number: INPLASY2020110093; INPLASY DOI number: 10.37766/inplasy2020.11.0093 Available at: https://inplasy.com ).